Dinamika Kelompok Peternak Sapi Potong Binaan Universitas Gadjah Mada di Propinsi Daerah Istimewa Yogyakarta - Andarwati, Siti; Guntoro, Budi; Haryadi, F. Trisakti; Sulastri, Endang (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
This study aimed to analyze the dynamics of cattle farmer groups assisted by Universitas Gadjah Mada (Faculty of Animal Science) in Yogyakarta Province. The total number of respondents were 77 farmers of cattle farmer groups. The tool used was a questionnaire that has proven validity and reliability. This study was conducted by survey method through the stages of preparation and execution. In the preparation phase carried out the determination of groups and cattle farmer samples using pusposive random sampling. The results showed that the dynamics of cattle farmer groups assisted by Universitas Gadjah Mada in Yogyakarta Province included in the high category. The highest group dynamics was Ngudi Barokah Group in Kulonprogo (equal to 82.48%), followed by the Sido Kumpul Group in Bantul (81.92%), then Bayu Andini Group in Sleman (77.22%), and Lembu Lestari Group in Gunungkidul (73.02%). Constituent elements of the group dynamics of goals, group structure, function assignments, development, cohesiveness, atmosphere and effectiveness of the group had a high level, while the group pressure was ini medium level.